Prenatal Yoga terhadap Nyeri Punggung pada Ibu Hamil Trimester III - Nainggolan, Ida Rosmauli; Lisviarose, Lisviarose; Nadia, Fatma; Aifa, Wira Ekdeni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effectiveness of prenatal yoga on back pain in third-trimester pregnant women at the Batang Gansal Community Health Center in Indragiri Hulu Regency. This study used a quantitative approach with a quasi-experimental design with a one-group pretest-posttest approach. The results showed that bivariate analysis using the Wilcoxon signed-rank test yielded a p-value of 0.000 < 0.05. In conclusion, prenatal yoga is effective in reducing back pain in third-trimester pregnant women at the Batang Gansal Community Health Center in Indragiri Hulu Regency. Keywords: Third-Trimester Pregnant Women, Back Pain, Prenatal Yoga